PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DESA DONGI KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Ikbal, Muhammad; A, Abdul Jabbar (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
It is very important to know community participation in the development planning of the Dongi village, Pitu Riawa District, Sidrap Regency. The study population was 17 years and above, namely 1,335 people. Data collection techniques used in this study were observation, questionnaires and interviews. The collected data is then used the method of quantitative analysis techniques with frequency tables. This study was conducted using a random sampling technique, using the Yamane formula with an error rate of 10% to produce 95 respondents. The results showed that the level of community participation in the development planning of the Dongi village in Pitu Riawa District, Sidrap Regency was in the category (Consultation) with a value of 81.5%, very good category.